Análise da paisagem da área de Proteção Ambiental Estadual do Rio Pandeiros, MG : subsídios para o manejo e conservação da fauna - Dias, Lívia Caroline César (Universidade Federal de São Carlos, 2017)
The advancement of human occupation and the evolution of its many activities have put many ecosystems at risk. The loss of native vegetation to agricultural practices has resulted in the fragmentation of habitats, which has serious consequences for biodiversity. Protected areas exist to try to avoid these interferences, but enforcement is not always effective and can avoid impacts. This scenario makes fundamental the analysis of the landscape of protected areas in macro-scale in order to try to predict and to reverse the impacts resulting from the expansion of the anthropic occupation. In view of these considerations, this dissertation aimed to obtain information about the landscape of the State Environmental Protection Area Rio Pandeiros (PSA Pandeiros), through the use of structural indexes of the landscape. The information was inserted and analyzed in Geographic Information Systems (GIS). The landscape structure was evaluated through the land use and land cover dynamics of PSA Pandeiros in 1995 and 2015. The evaluation of priority areas for PSA conservation was evaluated through the application of landscape metrics based on the results of the use and coverage evaluation from the land. And the evaluation of the location of ecological corridors for the PSA area was carried out based on the analysis of PSA connectivity potential from the results of the landscape metrics. The results showed that agricultural activities have strong influence structure of the landscape, mainly the pasture. The advancement of agricultural practices has made the landscape of the PSA suffer some degree of fragmentation which if not controlled will have serious consequences for the local biodiversity. The PSA still presents some fragments that have been considered high conservation areas due to their size and shape, are essential areas for actions that encourage the protection of the PSA. The analysis of the location of the ecological corridors showed that the proposed corridors are located in conservation priority areas and, therefore, their consolidation is necessary so that the fragmentation process of the PSA begins to be reversed and that the PSA may in the near future have A more connected landscape to ensure the 26 species of medium and large mammals found in the PSA and all the biodiversity that is interconnected.
Keywords: Dinâmica temporal; Fragmentação; Métricas da paisagem; Conectividade; Biodiversidade; Temporal dynamics; Fragmentation; Landscape metrics; Connectivity; Biodiversity; CIENCIAS BIOLOGICAS